Comparison of Financial Performance Before and After IPO (A Study on PT Saraswanti Anugerah Makmur Tbk - Stock Code SAMF) - Ardianto, Arif; Zalizar, Lili (Syntax Corporation, 2025)
Initial Public Offering (IPO) is a strategic step taken by companies to raise fresh capital, enhance liquidity, and improve their financial structure to support growth and expansion. PT Saraswanti Anugerah Makmur Tbk (SAMF), operating in the fertilizer industry, conducted an IPO in 2020 with the expectation of strengthening its market position and improving financial performance. This study aims to analyses SAMF's financial performance before and after the IPO by comparing various financial ratios, including profitability, liquidity, solvency, and operational efficiency. The research uses a quantitative approach with a comparative analysis, comparing the company’s financial data over two periods: four years before the IPO (2016–2020) and four years after the IPO (2020–2024). The results show that the IPO had a significant positive impact on SAMF's financial performance, particularly in the areas of liquidity and profitability. However, the company also faced challenges in managing operational costs and fluctuations in raw material prices, which affected overall performance. This study is expected to provide empirical contributions to understanding the impact of IPOs on the financial performance of companies in the fertilizer industry in Indonesia, as well as offering recommendations for companies planning to conduct an IPO.